Identification of Teachers and Students’ Readiness to E-Learning Implementation - Amalia, Ravitya Rizki; Anggoro, Subuh; Eka, Karma Iswata (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
The purpose of this study is to determine the readiness to implement e-learning in school, parents, and students at SD UMP, seen from the readiness of human resources, finance, and technology skills. The research method used is qualitative research with descriptive method. Participants in this study included a principal, 15 teachers, and 32 students, and the data were collected through observation, interviews, and documentation. This study shows that principals and teachers are ready for implementing e-learning from the side resources, finance, and technological skill. However, students and their parents have unprepared for it. They need more time to adapt the e-learning and the allocation their expenditure to it.